Day Workers, Main Heirs: Gender and Class Domination in the Parishes of Mourisca and Beba - González, Susana de la Gala; Roseman, Sharon R. (Anthropologica, 2022)
In this article, I focus on class and gender domination in the rural Galician parishes of Mourisca and Beba during the first half of the 20th century. My ethnographic and archival data demonstrate that the broader socio-economic context that affected women’s and men’s lives is similar in both parishes but that there are also significant personal, familial and regional differences that must be considered with respect to both the two field sites and the lives of distinct individuals in each locale. The two life stories that are incorporated into my discussion of the two parishes illustrate only two possible life trajectories for rural Galician women born during the first half of this century: Pepita’s effort to earn day wages and to be a labradora (landed peasant agriculturalist) in Mourisca and Maria’s failed attempt to marry a main heir in Beba.